Profile of military police officers with occupational stress - Menezes , Marcos Vinicius de Mendonça (2022)
Objective: To describe the psychosocial profile of military police officers with occupational stress. Methods: This was an exploratory, cross-sectional, quantitative study involving a non-probability sample. The study population comprised military police officers in the municipality of Aracaju, state of Sergipe. A minimum sample size of 176 participants was calculated, considering a sampling error of 5% and a confidence level of 95%. Two different questionnaires were applied: the first one focused on collecting  sociodemographic and occupational data; the second was Lipp’s Inventory of Stress Symptom for Adults (Inventário de Sintomas de Stress para Adultos de Lipp – ISSL), which identifies the presence and stage of stress (alarm, resistance and exhaustion) in the participants. Results: Of the interviewees, 32.4% were in some stage of stress; the main stressor was the police work itself. Stress was present in individuals of varying ages. Overall, military police officers with stress were male, married, had higher education, consumed alcohol, engaged in physical activity, worked full time, were partially satisfied with their jobs, but dissatisfied with the salary. Conclusion: The prevalence of military police officers with stress observed in this study can be harmful to society, to the professionals themselves, and to the police institution. There is a need for institutions to offer psychological support to this population.